2018
DOI: 10.1177/1358863x18754694
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in magnetic resonance imaging for peripheral artery disease

Abstract: The global burden of peripheral artery disease (PAD) is significant. This has led to numerous recent advances in magnetic resonance imaging (MRI) techniques in PAD. Older techniques such as time of flight MRI or phase contrast MRI are burdened by long acquisition times and significant issues with artifacts. In addition, the most used MRI modality, contrast-enhanced MR angiography (CE-MRA) is limited by the use of gadolinium contrast and its potential toxicity. Novel MRI techniques such as arterial spin labelin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 81 publications
(114 reference statements)
0
31
0
Order By: Relevance
“…Understanding the relationship between microvascular pathology and micro-perfusion offers a unique opportunity for the development of non-invasive diagnostic evaluation of PAD limbs and may have great utility in the assessment of the efficacy of different therapies. Furthermore, non-invasive imaging modalities, such as contrast-enhanced ultrasonography [ 31 , 32 , 35 ] and magnetic resonance imaging [ 37 , 38 ], could enhance our understanding of the functional alterations of the microvasculature of PAD limbs. Understanding PAD microvascular pathology may offer opportunities for more individualized therapies, which may include angiotensin-inhibitors, anti-hypertensives, statins, and DM medications, and may aid in the identification of patients who are likely to experience significant disease progression and need more aggressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the relationship between microvascular pathology and micro-perfusion offers a unique opportunity for the development of non-invasive diagnostic evaluation of PAD limbs and may have great utility in the assessment of the efficacy of different therapies. Furthermore, non-invasive imaging modalities, such as contrast-enhanced ultrasonography [ 31 , 32 , 35 ] and magnetic resonance imaging [ 37 , 38 ], could enhance our understanding of the functional alterations of the microvasculature of PAD limbs. Understanding PAD microvascular pathology may offer opportunities for more individualized therapies, which may include angiotensin-inhibitors, anti-hypertensives, statins, and DM medications, and may aid in the identification of patients who are likely to experience significant disease progression and need more aggressive therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Once a ‘control’ scan is obtained without tagging of the arterial blood, we can measure the signal difference of the tagged blood flow from the untagged image. The difference between these two images reflects the amount of tagged blood that has been delivered to the imaging region and, with appropriate tagging and imaging methods, reflects local tissue blood flow [ 72 , 73 ]. Zun et al showed that ASL CMR detects a clinically relevant increase in MBF with vasodilation and these measurements were consistent with ranges established by quantitative PET [ 73 ].…”
Section: Review Of Non-invasive Modalities For Cmd Assessmentmentioning
confidence: 99%
“…In ASL, arterial blood is used as an endogenous contrast agent by magnetically labeling the inflowing blood with radiofrequency pulses. Perfusion contrast is given by the difference in magnetization between a labeled and unlabeled control image induced by the exchange of magnetization at tissue level [18]. Because most ASL MRI techniques acquire the perfusionweighted images at a fixed time after the initial labeling of the arterial blood, it might be that the magnetic label may not reach the imaging plane, leading to an underestimation of peripheral blood flow.…”
Section: Technical Backgroundmentioning
confidence: 99%